Lag-times between lympho-proliferative disorder and clinical diagnosis of chronic lymphocytic leukemia (CLL): a prospective analysis using plasma soluble CD23. - Kaaks, R; Sookthai, D; Luczynska, A; Oakes, C; Becker, S; Johnson, T; Johansson, A; Melin, B; Sjöberg, K; Trichopoulos, D; Trichopoulou, A; Lagiou, P; et al. (2014)
Background:CLL is a chronic disease that often progresses slowly from a precursor stage, monoclonal B-cell lymphocytosis (MBL), and that can remain undiagnosed for a long time. Methods:Within the European EPIC cohort, we measured pre-diagnostic plasma sCD23 for 179 individuals who eventually were diagnosed with CLL and an equal number of matched control subjects who remained free of cancer. Results: In a very large proportion of CLL patients plasma sCD23 was clearly elevated 7 or more years before diagnosis. Considering sCD23 as a disease predictor, the area under the ROC curve (AUROC) was 0.95 [95% CI (0.90, 1.00)] for CLL diagnosed within 0.1-2.7 years after blood measurement, 0.90 [0.86-0.95] for diagnosis within 2.8-7.3 years, and 0.76 [0.65-0.86] for CLL diagnosed between 7.4 and 12.5 years. Even at a 7.4-year and longer time interval, elevated plasma sCD23 could predict a later clinical diagnosis of CLL with 100% specificity at >45% sensitivity. Conclusions:Our findings provide unique documentation for the very long latency times during which measurable B-cell lympho-proliferative disorder exists prior to the clinical manifestation of CLL. Impact:Our findings have relevance for the interpretation of prospective epidemiologic studies on the causes of CLL in terms of reverse causation bias. The lag-times indicate a time frame within which an early detection of CLL would be theoretically possible.